(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
The talent management is continual processes that involve maintaining &recruiting high quality workers, enhancing abilities, & motivating to improve the performances on a regular basis. Primary goal of the talent management is developing a motivated staff that remains with company for long haul. The talent management helps employees feeling engaged & motivated, allowing to set out effort necessary to meet company’s objectives, resulting in improved business performance & customer satisfaction. Lack of data connecting different expert claims is discussed in this article, also issue of talent management explanation. Studies that retain a methods-oriented explanation centered on planned talent management will highlighted later. In last section, we suggest some upcoming possibilities in related research to further develop field of talent management & to better connect it to massive amount of activity in the strategic human resource management.